ROUTLEDGE HANDBOOK OF SPORT EXPERTISE - Baker, Joseph; Farrow, Damian, 1970- (Routledge, 2017)
Understanding and developing expertise is an important concern for any researcher or practitioner working in elite or high performance sport. Whether it's identifying talented young athletes or developing methods for integrating cutting-edge sport science into daily coaching practice, scientists, coaches and researchers all need to understand the skills, characteristics, and knowledge that distinguish the expert performer in sport. The Routledge Handbook of Sport Expertise is the first book to offer a comprehensive overview of current research and practice in the emerging field of sports expertise. Adopting a multi-disciplinary, multi-faceted approach, the book offers in-depth discussion of methodological and philosophical issues in sport expertise, as well as the characteristics that describe sporting ‘experts’ and how they can be facilitated and developed. Exploring research, theory and practice, the book also examines how scientists and practitioners can work together to improve the delivery of applied sport science